A rapid and high-throughput multiplex genetic detection assay for detection, semi-quantification and virulence genotyping of Helicobacter pylori in non-invasive oral samples - Chi, Wenjing; Wang, Su; Liu, Tao; Jiang, Wenrong; Ding, Li; Miao, Yingxin; Yang, Feng; Zhang, Jinghao; Ji, Danian; Xiao, Zili; Zhu, Haowei; Wu, Yong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Aim This study established a high-throughput multiplex genetic detection assay (HMGA) for rapid identification, semi-quantification and virulence analysis of Helicobacter pylori directly from the clinical non-invasive oral samples. Methods The gastric mucosa and oral samples were collected from 242 patients in Shanghai from 2021 to 2022. All the samples were detected by routine clinical tests for H. pylori and Sanger sequenced for inconsistent results. A new multiplex PCR assay providing results within 4 hours was designed and optimized involving fluorescent dye-labeled specific primers targeted 16S rRNA gene, semi-quantitative gene ureC and 10 virulence genes of H. pylori. Semi-quantification was carried out by simulating the serial 10-fold dilutions of positive oral samples, and the H. pylori loads in different clinical samples were further compared. The mixed plasmids of virulence genes vacA s1, vacA m1 and vacA m2 were used to evaluate the performance on different genotypes. The consistency of 10 virulence genes in gastric mucosa, saliva, mouthwash and dental plaque of H. pylori-positive patients was compared. Results The non-invasive HMGA was highly specific for detection of all 12 targets of H. pylori and human internal reference gene β-globin, and the sensitivity to all target genes could reach 10 copies/μL. Compared with routine clinical tests and sequencing, non-invasive HMGA has a high level (>0.98) of sensitivity, specificity, accuracy, PPV, NPV and kappa coefficient for direct detection of H. pylori in oral samples. Moreover, by detecting peak area levels of ureC, it was confirmed that the H. pylori loads in gastric mucosa were significantly higher than those of the three kinds of oral samples (p<0.05). We also found that 45.0% (91/202) of patients had different H. pylori virulence genes in different oral samples. The concordance of positive detection rates of each virulence gene between saliva and gastric mucosa was more than 78% (p<0.05). Conclusion The non-invasive HMGA proved to be a reliable method for the rapid H. pylori identification, semi-quantification and detection of 10 virulence genes directly in oral samples, providing a new idea for non-invasive detection of H. pylori.